The Dilemma of Auditors’ Professional Ethics in Enhancing Audit Effectiveness - Nur Sakinah Irman; Sumarlin; Della Fadhilatunisa (Journal of Applied Taxation and Policy, 2026)
This study examines the professional ethical dilemmas faced by internal auditors within the Internal Supervisory Unit (SPI) at UIN Alauddin Makassar and their impact on the effectiveness of internal audits. This research employs a qualitative method with a phenomenological approach, and data were collected through interviews. The findings reveal that the dual roles of auditors can actually create a positive synergy between academic responsibilities and internal audit functions. Auditors face negative stigma from auditees, who perceive them as "watchdogs" or faultfinders. Auditors reported no pressure from university leadership, as all matters are entrusted to SPI. However, when audit findings directly involve the leadership, there are instances where the leadership requests that such findings be omitted from the audit report. In addition, auditors experience ethical dilemmas when auditing auditees with whom they have personal relationships. The presence of SPI and the strict application of professional ethics have contributed to enhancing the effectiveness of audits.